2010
DOI: 10.1186/1471-2148-10-124
|View full text |Cite
|
Sign up to set email alerts
|

Historical spatial range expansion and a very recent bottleneck of Cinnamomum kanehiraeHay. (Lauraceae) in Taiwan inferred from nuclear genes

Abstract: BackgroundSpecies in the varied geographic topology of Taiwan underwent obvious demographic changes during glacial periods. Cinnamomum kanehirae has been exploited for timber and to obtain medicinal fungi for the past 100 years. Understanding anthropogenic factors influencing the demography of this species after the last glacial maximum (LGM) is critically important for the conservation of this species.ResultsPopulations of C. kanehirae were classified into four geographic regions: northwestern (NW), west-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 78 publications
2
50
1
Order By: Relevance
“…The lower level of genetic diversity in C. kanehirae is the result of the stochastic losses of genetic polymorphisms. This observation is consistent with the results of Kuo et al (2010) and Liao et al (2010) studies. Positive F IS were found in all populations except LI, which is interpreted that inbreeding may have also contributed to the decrement of genetic diversity of C. kanehirae.…”
Section: Locussupporting
confidence: 83%
See 1 more Smart Citation
“…The lower level of genetic diversity in C. kanehirae is the result of the stochastic losses of genetic polymorphisms. This observation is consistent with the results of Kuo et al (2010) and Liao et al (2010) studies. Positive F IS were found in all populations except LI, which is interpreted that inbreeding may have also contributed to the decrement of genetic diversity of C. kanehirae.…”
Section: Locussupporting
confidence: 83%
“…This also leads to a decrease of genetic variation and population structure. Kuo et al (2010) examined the genetic patterns of cpDNA in C. kanehirae and found that its genetic variation is smaller than that of other tree species in Taiwan, which is also manifest in its nuclear genes (Liao et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Plant material and DNA extraction: During winter (October-January) in Taiwan, 23 fresh leaf samples of C. micranthum were collected for chemical analyses from Taipei, Ilan, and Natou, while 23 C. kanehirae samples were collected from 13 sites throughout the Taiwan island, including sampling areas covered by previous studies (Lin 1993;Liao et al 2010). Wood materials (with height over 3 m) were collected from 12 individuals from Fushan Botanical Garden in Ilan and Liouguei Research Center in Kaohsiung city of Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…This tree is difficult to find in the wilderness because of its unrestrained illegal logging (Lin et al 1997;Hung et al 2014). Thus, C. kanehirae is an endangered wood species, which also plays an important economic and ecological role in Taiwan (Liao et al 2010;Cheng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation